Pendekatan Culturally Responsive Teaching (Crt) Dalam Pembelajaran Matematika Di Kelas Xi Sma - Hidayah, Hidayah (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the implementation of the Culturally Responsive Teaching (CRT) approach in mathematics learning on the topic of composition of functions in Grade XI of senior high school. The approach was applied to connect mathematical concepts with local cultural contexts, making the learning experience more meaningful. This research employed a descriptive qualitative method involving 25 students from Grade XI as participants. Data were collected through observation, unstructured interviews, written tests, and documentation, then analyzed descriptively using source triangulation. The results showed that the implementation of CRT increased students’ motivation, engagement, and conceptual understanding. The use of local cultural contexts—such as the making of baju cele (traditional Ambonese attire), papeda (sago porridge), and sagu tumbu (a traditional Maluku snack)—helped students grasp the concept of composition of functions in a more concrete and relevant way. However, challenges remained, including teachers’ difficulties in linking mathematical concepts to local culture and time constraints during implementation. Overall, the Culturally Responsive Teaching (CRT) approach proved effective in fostering meaningful learning, as it bridges academic knowledge with students’ cultural identity in line with the spirit of the Merdeka Curriculum.